Answer:
Explanation:
Simplifying
25m + 22 = 9m
Reorder the terms:
22 + 25m = 9m
Solving
22 + 25m = 9m
Solving for variable 'm'.
Move all terms containing m to the left, all other terms to the right.
Add '-9m' to each side of the equation.
22 + 25m + -9m = 9m + -9m
Combine like terms: 25m + -9m = 16m
22 + 16m = 9m + -9m
Combine like terms: 9m + -9m = 0
22 + 16m = 0
Add '-22' to each side of the equation.
22 + -22 + 16m = 0 + -22
Combine like terms: 22 + -22 = 0
0 + 16m = 0 + -22
16m = 0 + -22
Combine like terms: 0 + -22 = -22
16m = -22
Divide each side by '16'.
m = -1.375
Simplifying
m = -1.375